Computed Tomography with Intravenous Contrast is Not Associated with Development of Acute Kidney Injury in Severely Injured Pediatric Patients. Issue 1 (January 2019) - McGaha, Paul K.; Johnson, Jeremy; Garwe, Tabitha; Sarwar, Zoona; Motghare, Prasenjeet; Daly, William; Letton, Robert
Data for the incidence of acute kidney injury (AKI) related to intravenous contrast administration in the pediatric trauma population are limited. Obtaining a creatinine value before elective CT scans is a relatively accepted standard of care. We sought to determine whether there was any significant difference in the incidence of AKI between severely injured patients who received IV contrast and those who did not. We reviewed data from the trauma registry at our Level I pediatric trauma center. We limited the patients to severely injured pediatric traumas (<15 years old) directly transported from the scene of injury with a creatinine level measured on arrival. Two hundred and eleven patients were included in the study. AKI was defined by the criteria of the AKI Network. We then compared incidence of AKI in those who received a CT scan with IV contrast with those who did not receive IV contrast. The two groups were comparable in age, gender, Glasgow Coma Scale, Injury Severity Score, mean creatinine on arrival, and mean creatinine post–CT scan/arrival. There was no significant difference in AKI between the two. In a subgroup analysis of patients presenting in shock, there was no significant difference in AKI. Our study suggests that IV contrast is not associated with the development of AKI in severely injured pediatric trauma patients. Although obtaining a creatinine value before exposure is ideal, a CT scan with IV contrast in severely injured children should not be delayed to obtain a creatinine value.